The complete mitochondrial genome of the pentastomid Linguatula arctica (Pentastomida) from reindeer (Rangifer tarandus) in Northern Norway. Issue 3 (2nd July 2020) - Grau, José Horacio; Dunlop, Jason A.; Meixner, Martin; Tappe, Dennis; Gjerde, Bjørn
Abstract: Here, we present the first complete mitochondrial genome of the pentastomid Linguatula arctica collected from the nasal passages of a reindeer ( Rangifer tarandus ) in Norway. The full length mitochondrial genome of L. arctica, which measures 14, 789 bp in length, contains 13 protein-coding genes, 2 ribosomal RNA genes and 22 transfer RNA genes. A clear A + T bias is observed in the mitogenome of L. arctica with an overall base composition of 32.6% A, 27.5% T, 32.8% C, and 7, 1% G., and a GC content of 39.9%. The gene arrangement is identical to that of previously described pentastomid mitogenomes.